Evaluasi Kinerja Web Haji dan Umrah NSK Group Pekanbaru Perspektif Pengguna Menggunakan Framework Cobit 2019 - Efendi, Harisman; Muhammad Raihan; Diky Supadly; Nanda Kito Baguno; Megawati Megawati (Pusat Riset dan Inovasi Nasional, 2024)
This research is grounded in the importance of websites in providing services for Hajj and Umrah pilgrimages, reflecting the role of technological advancement in delivering information and facilities to pilgrims. The primary aim of this study is to understand the role of websites in facilitating Hajj and Umrah services and to evaluate their effectiveness in enhancing the experiences and satisfaction of pilgrims. A qualitative descriptive methodology was employed, gathering data through direct observation and questionnaires, supplemented by an analysis of relevant literature. The findings indicate that effective and user-friendly websites enhance pilgrim experiences and simplify the processes of booking, accommodation, and transportation. An analysis using the COBIT 2019 framework underscores the significance of IT management in improving website performance. The implications of this study highlight the need for continuous innovation and improvement in data security, incident management, and business process efficiency of websites to increase customer satisfaction and ensure the efficient and secure provision of Hajj and Umrah services.